Kontribusi Pendidikan Islam dalam Meningkatkan Kesadaran Hukum tentang Nafkah dalam Rumah Tangga - Ngadri, Ngadri; Sanusi Md Noh, Muhammad (Berasan: Journal of Islamic Civil Law, 2024)
This study discusses the contribution of Islamic education in increasing legal awareness about domestic maintenance. This research uses a literature study method by examining various sources such as books, scientific journals, ulama fatwas, and Islamic legal documents related to Islamic education and maintenance law. An analysis was carried out on Islamic education theory, the concept of legal awareness, and the study of Islamic family law to understand how Islamic education contributes to building an understanding of the obligation to provide for maintenance. The results of the study show that Islamic education plays a role in increasing understanding and compliance with the law of domestic maintenance. A curriculum that teaches Islamic family law in formal and non-formal educational institutions can strengthen individual awareness of rights and obligations in the family. However, the contribution of Islamic education is still influenced by teaching methods, family support, and social environment. The conclusion of this study confirms that Islamic education has a significant contribution in building awareness of the law of maintenance in the household. Therefore, it is necessary to strengthen the curriculum and learning strategies so that the understanding of Islamic family law can be more optimal.